Pendampingan Pembelajaran Akuntansi untuk Meningkatkan Kemampuan dan Keterampilan Siswa dalam Menyusun Kertas Kerja (Worksheet ) Perusahaan Jasa di SMAK St. Darius Larantuka - Maria Fatima B. Beribe; Abel Andisolo Sogen; Elisabeth Sasa Koten (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The purpose of implementing Community Service (PkM) is to overcome the problems faced by community service partners, namely difficulties in learning accounting for class XII SOS students at SMAK St. Darius Larantuka. This activity is also a follow-up to the previous study entitled "Analysis of Difficulties in Learning Accounting for the Sub-Material of Service Company Worksheets for Class XII SOS Students at SMAK St. Darius Larantuka in the 2024/2025 Academic Year". The form of community service carried out is training and assistance in compiling worksheets for service companies. The participants involved were 20 students from class XII SOS 2. This activity was carried out in three stages, namely: 1) delivery of material regarding worksheets for service companies, 2) practice of compiling worksheets, and 3) evaluation of work results. The material was delivered collaboratively by the economics subject teacher, Mr. Abel Andisolo Sogen, S.Pd, and the community service lecturer, Mrs. Maria Fatima B. Beribe, M.Pd. In the practice stage, participants were asked to compile worksheets based on the case studies that had been submitted. During this process, participants were assisted by the service team until they achieved the expected results. To measure the participants' abilities and skills in compiling working papers, they were then asked to complete different case study questions independently. The results of the participants' work were analyzed using qualitative analysis methods, which showed an increase in understanding and skills during independent practice compared to during mentoring. This is reflected in the scores obtained by the participants, which ranged from 85 to 95, and reached the target of 90% of what the service team wanted. However, there were several participants who had difficulty in compiling working papers due to lack of accuracy in the calculations, so that the calculation results in the Balance Sheet column were not balanced.